Less metal fluxes than expected from fibrous marine sediments. (January 2020) - Frogner-Kockum, Paul; Kononets, Mikhail; Apler, Anna; Hall, Per O.J.; Snowball, Ian
Abstract: Deposits of fibrous sediment, which include fiberbanks and fiber-rich sediments, are known to exist on the Swedish seafloor adjacent to coastally located former pulp and paper industries. These deposits contain concentrations of hazardous substances that exceed national background levels and contravene national environmental quality objectives (EQOs). In this study of metal fluxes from fibrous sediments using benthic flux chamber measurements (BFC) in situ we obtained detected fluxes of Co, Mo, Ni and Zn, but no fluxes of Pb, Hg and Cr. The absence of fluxes of some of the analyzed metals indicates particle bound transport of Pb, Cr and Hg from fiberbanks even though Hg might become methylated under anoxic conditions and, in that case, may enter the food chain. We found less metal fluxes than expected and thus emphasize the importance of in-situ flux measurements as a compliment to sediment metal concentrations within risk assessments of contaminated sediments.